Kemampuan Pemecahan Masalah Matematika ditinjau dari Curiosity Siswa melalui Penerapan Model Guided Discovery Learning Berbantuan Pendekatan Kontekstual Pada Materi Penyajian Data (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Problem-solving ability is a crucial skill in mathematics learning. However, many elementary school students struggle with mathematical problem-solving, particularly on data presentation materials. This research aims to investigate the improvement of mathematical problem-solving abilities and student curiosity through the application of Guided Discovery Learning (GDL) with contextual approach support. This mixed-method research involved 44 respondents: 21 students from the experimental group (SD Negeri 2 Tunggulsari) and 23 students from the control group (SD Negeri 2 Sumur). The experimental group received learning using GDL with contextual approach, while the control group received conventional learning. Data were collected through pre-test, post-test, curiosity questionnaires, and interviews. Results showed that the experimental group achieved an average post-test score of 80.71 compared to the control group's 72.39 (t = 3.180, p = 0.003), with 86% of experimental group students achieving mastery. Additionally, student curiosity increased significantly from 47.62% to 79.52% after GDL implementation. The normalized gain score was 0.59 (moderate category), indicating that GDL with contextual approach effectively improved both mathematical problem-solving abilities and student curiosity. This research provides evidence that GDL with contextual approach is an effective alternative learning method for improving mathematics learning outcomes at the elementary school level.